The impact of donor policies in Europe: a steady increase, but not everywhere - Blok Geke A (BMC Health Services Research, 2008)
Abstract Background Transplantable organs are scarce everywhere. Therefore, countries have developed policies to support the efficient use of potential donors. Nevertheless, the shortage of organs remains. Were these policies in vain? The aim of this study is to assess the impact of donor policies on donor procurement in 10 Western European countries from 1995 to 2005. Method To assess the impact of the donor policies we studied the conversion of potential donors into effectuated donors. 80% of the donors died from CVAs or a (traffic) accident. We considered these mortality rates to be a good proxy for potential donors. Here we call the conversion of potential donors into actual donors 'the donor efficiency rate by proxy'. Results The mortality rates for CVA and (traffic) accidents have decreased in the countries under study. At the same time, in most countries the donor efficiency rates have steadily increased. The variance in donor efficiency rates between countries has also increased from 1995 to 2005. Four countries introduced a new consent system or changed their existing system, without (visible) long-term effects. Conclusion The overall increase in donor efficiency means that the efforts to improve donor policies have paid off. However, substantial differences between countries were found. The success of donor policies in terms of the number of absolute donors is blurred by the success of policies on traffic safety and CVA treatment. It remains unclear which specific policy measures are responsible for the increase in donor efficiency rates. This increase is not related to having a presumed consent system. Furthermore, an analysis of countries that introduced a new consent system or changed their system showed no effect on donor efficiency.